Electron radiation effects on threshold voltage and drain current characteristics of commercial power metal oxide semiconductor devices - Abubakkar, Sheik Fareed Ookar (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
Microelectronic power converters such as buck and boost converters are required to be radiation tolerant to exposure of radiation, including electron radiation because of its significant applications in the satellite and space system. Each components of the buck converter design required to be radiation tolerant. The switching transistor is among one of the component significant to be more radiation hardened as it contribute to the efficiency of the power converters. This thesis examines electron radiation effects on threshold voltage and drain current characteristics of VDMOSFET switching transistor and its corresponding effects in buck converter. This thesis comprises into two parts. The first part presents the study of threshold voltage and drain current characteristics of n-channel and p-channel VDMOSFETs before and after electron beam radiation. Analysis on the electrical characteristics shows that 3MeV energy with the dose level of 50KGy, 100KGy and 200KGy is capable in creating ionization damage in the selected VDMOSFETs. Due to this the threshold voltage of all the n-channel and the p-channel VDMOSFETs shifted negative and the drain current degraded for both the n-channel ZVN4424A, ZVNL120, 2N700 and the p-channel VDMOSFET ZVP4424A,ZVP3306A, ZVP2106A. As the switching characteristics correlates with electrical behaviors, the second part of thesis studied about the switching performance of VDMOSFET with buck converter applications. Analysis on the buck converter output voltage were performed before and after VDMOSFET irradiation. A buck converter with the n-channel switching transistor shows its output voltage increased corresponding to the 5 orders of increase in drain current in the n-channel VDMOSFET after radiation. A buck converter with the p-channel switching transistor shows its output voltage decreased corresponding to 2 orders of decrease in the drain current of the VDMOSFET after radiation.